Probiotics Supplementation During Pregnancy - Muhammad Ahsan, Muhammad Ahsan; Yohana, Yohana (The Indonesian Journal of General Medicine, 2024)
Background: The literature on probiotics supplementation during pregnancy reveals a compelling narrative regarding their potential benefits for maternal and neonatal health. The synthesis of findings from various studies highlights the multifaceted role of probiotics in improving perinatal outcomes, modulating gut microbiota, and enhancing maternal health. Literature Review: The integrative review by VandeVusse, Hanson, and Safdar (VandeVusse et al., 2013) underscores the positive maternal outcomes associated with prenatal probiotic ingestion, including reduced rates of bacterial vaginosis and lower incidences of gestational complications such as preeclampsia and gestational diabetes. Building on this foundation, Vitacolonna et al. (Vitacolonna et al., 2022) delve deeper into the implications of probiotics in mitigating adverse maternal and neonatal outcomes. Chen et al. (Chen et al., 2019) further explore the relationship between probiotics, gut microbiota, and immune status during pregnancy, noting the prevalence of dysbiosis and its association with gestational diabetes and obesity. The systematic review by Pérez-Castillo et al. (María Pérez-Castillo et al., 2021) evaluates the reporting of perinatal outcomes in randomized controlled trials involving probiotics, stressing the necessity for rigorous study designs and standardized dosages to draw robust conclusions. Conclusion: In conclusion, the body of research reviewed demonstrates that probiotics supplementation during pregnancy holds promise for improving maternal health outcomes and potentially benefiting offspring. However, it also emphasizes the need for further investigation into the optimal strains, dosages, and timing of probiotic interventions to fully understand their mechanisms and establish standardized guidelines for clinical practice.